Considering Shear Behavior of Beam-Column Connections to Assess the Seismic Performance of RC Frames Subjected to Freeze-Thaw Cycles. Issue 3 (23rd February 2021) - Qin, Qing; Zheng, Shansuo; Dong, Liguo; Hou, Piji; Wang, Feng
ABSTRACT: Freeze-thaw of concrete is significantly responsible for serious damage to RC buildings, which may result in premature failure with little warning. Therefore, it is necessary to consider the effects of freeze-thaw environment when assessing seismic performance for RC structures. In this study, pseudo-static experiments of interior beam-column joints were conducted in terms of different axial compression ratios and the number of freeze-thaw cycles (FTC). Based on the experimental results, the effects of freeze-thaw were mathematically modeled using a reduced envelope and a parameter of cyclic deterioration for the joint shear–strain relationships. The constitutive parameters of joint panels were defined by transforming the shear–strain relation into the moment–rotation relation of a shear spring. Finally, a numerical model of a beam-column joint was proposed in order to predict its shear behavior after being subjected to FTC. The numerical model was well validated by the experimental results of two RC beam-column joint test series. As an application to RC structures, model calculations were applied to five-story and three-bay RC frames of 0 and 30 years, respectively.